Diferentes tipos de sustrato en el comportamiento agrónomico de plantas de sacha inchi (plukenetia volubilis linneo l) en vivero, en la Zona Quinindé - Arguello Cedeño, Angel Robinson (2015)
The work was carried out in the enclosure the Duana Km 8,5 road to the Fifth, belonging to the county of Emeralds, canton Quinindé, property The Laurels, located between the coordinates 79° 27´ longitude west and 01° 06´ with one of latitude of 120 msnm. The objectives were to Evaluate the different sustrato types in the agronomic behavior of plants of Sacha Inchi (Plukenetia volubilis Linneo L) in nursery, in the area Quinindé, to settle down with which of the sustratos in study the biggest plant height is obtained, to establish the best sustrato type in the nursery stage with relationship to its diameter in the plant propagation Sacha Inchi and to formalize in that treatment carried out in this study the biggest germination percentage is obtained. The experimental design was totally at random of type (DCA). to determine the differences among the treatments he/she was carried out the test from Tukey to 0.5% of probability. Four treatments T0 was used Without sustrato, T1 Husk of rice + field earth, T2 Cracked of sacha Inchi + common earth and T3 raft Sawdust + field earth and four repetitions. The variables were analyzed germination percentage, plant height, diameter of the shaft, number of leaves, root longitude, root weight, cotyledon height and percentage of mortality. The adults and smaller obtained results were germination T2 97.50% and T3 83.75%, plant height, to the 15 days T2 9.87 cm and T3 7.27 cm; to the 30 days T2 20.55 cm and T3 14.38 cm; to the 45 days T2 45.13 cm and T1 25.288 cm. Diameter of the shaft to the 15 days T2 1.97 cm and T0 1.86 cm, 30 days T2 2.00 cm and T3 1.95 cm, 45 days T2 2.18 cm and T1 2.06 cm. Number of leaves 15 days T2 1.80 und and T3 0.65 und, 30 days T2 4.95 und and T1 3.80 und, 45 days T2 10.70 und and T1 6.75 und. Root longitude T0 41.65 cm and T1 30.78 cm. root Weight T2 19.70 gr. and T3 7.00 gr. Cotyledon height 15 days T2 8.14 cm and T3 4.47 cm 30 days T2 10.40 cm and T3 8.73 cm, 45 days T2 10.59 cm and T3 8.81 cm, percentage of mortality T0 8.75%.